Suplementasi Probiotik dan Temulawak pada Ayam Pedaging terhadap Populasi Salmonella sp dan kolesterol darah (PROBIOTICS AND TEMULAWAK SUPPLEMENTATION ON BROILER CHICKENS AGAINST SALMONELLA SP POPULATION AND BLOOD CHOLESTEROL LEVEL) - Alipin, Kartiawati; Safitri, Ratu; Kartasudjana, Ruhyat (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
Probiotics is a live microbial feed supplements that improve the microbial balance in the digestivetract of cattle host. Temulawak (Curcuma xanthorrhiza Roxb) is one of native Indonesian spices that areuseful for prevention and treatment of human disease but also can be used for broiler chickens supplement.Bioactive contents known acting as an anti-bacterial, anti-inflammatory, and anti-fungal. The study wasconducted to determine the effects of probiotic and temulawak supplementation on population of Salmonellasp and broiler chickens blood cholesterol. This study used 300 DOC final stock. Probiotic concentration 109cell/mL administered through drinking water every day while of temulawak extract dose 0.25 g/L 0.50 g/Lonce a week, for five weeks. The variables measured were Salmonella sp populations and blood cholesterollevels. The results showed that combination administered of probiotics with temulawak dose 0.50 g/Ldecreased of population of Salmonella amount to 87.04% and decreased of blood cholesterol amount21,48% at administered of probiotics with temulawak dose 0,25 g/L. The conclusions of this study showedthat the percentage decrease of Salmonella sp population and blood cholesterol levels in combinationprobiotic and temulawak supplementation so that broiler produced is safe for consumption.
Keywords: probiotics, temulawak, Salmonella, blood cholesterol, broiler